(untitled) (Community Based Medical Journal, 2025)
Lupus vulgaris is the most common type of cutaneous tuberculosis in adults with most varied manifestation. A characteristic feature of lupus vulgaris is its extremely chronic course with slow but steady growth of the lesions over a period of many years, even decades. Head and neck are the sites commonly affected in European countries. However, in Indian subcontinent, the buttocks, thighs, and legs are the common sites of involvement. A 36-year-old woman presented with large single plaque of 5 weeks duration over left buttock. The lesion was asymptomatic except for mild pain. Histopathologic examination revealed well defined epithelioid granulomas, some multinucleated giant cells including Langhans type of giant cells. Mantoux test was strongly positive with well-defined induration. This case is being reported because of its rarity and acute presentation. CBMJ 2025 January: Vol. 14 No. 01 P: 156-159